Implementasi Keperawatan Manajemen Nyeri Pada Pasien Hipertensi : Studi Kasus - Vilana, Elen; Sulistini, Rumentalia; Sulaiman, Sulaiman (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2024)
Background: Almost 1.13 billion people in the world have hypertension, meaning that 1 in 3 people in the world are diagnosed with hypertension and will continue to increase until 2025. So it is necessary to do a case study for this case because almost people with hypertension experience pain and need pain management. Methods : This type of research design uses a descriptive design in the form of a case study. The approach used is a nursing care approach which includes assessment, nursing diagnosis, planning, implementation, evaluation and documentation. The case study subjects used were 2 of the same patients, namely hypertensive patients with acute pain problems. This research was conducted at the Palembang Muhammadiyah Hospital in 2022. Results : The implementation of pain management nursing was carried out with the stages of observation, therapeutic, education, collaboration for both patients, all patients were given the same implementation and the problem was resolved for 3 days. Conclusion : The results of the study illustrate the need for pain management nursing interventions, namely deep breathing relaxation techniques to reduce pain in hypertensive patients with acute pain problems.